Canopy structure analysis for estimating forest regeneration dynamics and growth in Nothofagus pumilio forests - Martínez Pastur, Guillermo José (2011)
Introduction: Silviculture systems applied in Nothofagus pumilio forests are based on opening the canopy to stimulate natural regeneration by modifying light and soil moisture. The objective is to evaluate regeneration dynamics of N. pumilio along different forest canopy and solar radiation gradients. Materials and methods: Regeneration data and seed production were obtained in 98 permanent plots established in old-growth and harvested stands along a crown cover gradient (19–93%). Volumetric soil water content and basal area were also measured, while crown cover and solar radiation transmission were estimated using hemispherical photographs. Sapling height was modeled using plant age, crown cover, and solar radiation transmission of the stands as explanatory variables. Results: Natural regeneration dynamics were closely related to crown cover values, which determined seed production and the successful establishment and subsequent regeneration growth. Height growth was found to be related to crown cover and solar radiation transmission, where N. pumilio regeneration is optimized at intermediate crown cover levels (45% crown cover, 0.5 effective leaf area index, 26 W m² global radiation, and 65% percentage of global radiation). Conclusion: These findings can be used to develop new silvicultural methods or to adjust the current practices to ensure regeneration establishment and maximize height growth at the stand level.